Synthesis and Evaluation of Starch-Urea-Borate for Controlled Release Application - CHOWDARY, K.P.R.; MURALI KRISHNA, M.N. (Asian Journal of Chemistry, 2010)
The objective of the present investigation is to synthesize starchurea- borate, a new starch based polymer and to evaluate its application in controlled release (CR) and in the design of controlled release tablets of diclofenac and gliclazide. The release retarding efficiency of starchurea- borate was also compared with that of known polymers. Starchurea- borate (SUB) polymer was synthesized by gelatinization of starch in the presence of urea and borax. Matrix tablets of diclofenac (100 mg) and gliclazide (60 mg) were formulated employing starch-ureaborate polymer in different proportions of drug and polymer and the tablets were evaluated. With both diclofenac and gliclazide, release from the formulated matrix tablets was slow and spread over 24 h and depended on per cent polymer in the tablet. Release was diffusion controlled and followed zero order kinetics. Non-fickian diffusion was the drug release mechanism from the formulated tablets. Diclofenac release from matrix tablets formulated employing 33 % SUB (DF3) and gliclazide release from matrix tablets formulated employing 50 % SUB (GF4) was similar to that from the corresponding commercial SR tablets. Starch-urea-borate polymer was found suitable for the design of oral controlled release tablets of diclofenac and gliclazide. The order of increasing release retarding effect with various polymers was ethyl cellulose = guar gum > SUB > sodium CMC > HPMC. Starch-urea-borate is a better release retarding polymer than HPMC and sodium CMC for obtaining controlled release over 24 h.